Classifying and Characterizing the Evolution of the Minimum Orbit Intersection Distance for Near-Earth Asteroids - Shoucun Hu; Yuanyuan Chen; Xinran Li; Xiuhai Wang; Xuefeng Wang (The Planetary Science Journal)
In this paper, the minimum orbit intersection distances (MOIDs) of near-Earth asteroids (NEAs) over the next 200 yr are computed and analyzed in detail. It is shown that the MOID of an NEA relative to the Earth–Moon barycenter is usually a better metric for predicting a potential impact than that relative to the Earth. Subsequently, a novel MOID evolution index (MEI) spanning from 0.0 to 9.9 is proposed, and the orbits of NEAs are classified into 100 distinct categories by considering the variations of the MOID over time, which is useful for quickly screening and prioritizing hazardous asteroids for future research. Furthermore, it is demonstrated that a linear fitting to the MOID evolution provides a simple yet valid approach for most of the NEAs, which is useful for quickly estimating the MOID value without the need to perform an orbit propagation. As a result, a scheme with several parameters is proposed to characterize the MOID variations as well as the relative position information of the critical points along the orbits associated with the minimum distances. A database incorporating these parameters and the MEI values is therefore established for the cataloged NEAs, enabling the derivation of statistically constrained upper bounds for the secular MOID drift rate as a function of the semimajor axes. Finally, some special orbital configurations and dynamical mechanisms that may lead to a large deviation from the linear fit or multiple orbit crossings are also investigated, indicating the intricate nature in the patterns of MOID evolution for some NEAs.